2020
DOI: 10.1002/ccr3.2770
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand syndrome and lymphoproliferative disorders: A case report

Abstract: Acquired von Willebrand syndrome is a rare bleeding disorder often secondary to an underlying lymphoproliferative disorder. We report a case in whom response of both the acquired von Willebrand syndrome and smoldering multiple myeloma persist 14 months after daratumumab treatment discontinuation. K E Y W O R D Sacquired von Willebrand syndrome, bleeding, daratumumab, smoldering multiple myeloma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Data are scarce, but the clinical response of AWS generally precedes the first improvement of VWF biology, and sometimes occurs years before the normalisation of VWF biology, but the LRD/PRD may have responded quickly. 25,31,48,51 In our opinion, the absence of biological improvement of AWS in the context of a reduction of haemorrhagic syndrome and PRD/LRD response should not induce a modification of the treatment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Data are scarce, but the clinical response of AWS generally precedes the first improvement of VWF biology, and sometimes occurs years before the normalisation of VWF biology, but the LRD/PRD may have responded quickly. 25,31,48,51 In our opinion, the absence of biological improvement of AWS in the context of a reduction of haemorrhagic syndrome and PRD/LRD response should not induce a modification of the treatment.…”
Section: Discussionmentioning
confidence: 92%
“…AWS was often the unique reason to initiate malignancy treatment, notably in PRD, which emphasises the difficult choice to treat the underlying disorder because there is no test to firmly establish the link between AWS and LRD or PRD. There is no clear correlation between the clinical and biological severity of AWS, and severe biological AWS may be present for years without clinical impact, which makes treatment initiation of the underlying malignancy at the proper time even more difficult 25 . Strict education on these patients would be important to alert haematologists when new bleeding symptoms appear.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, lenalidomide is unlikely suited as a treatment in patients with an elevated risk of thromboembolism or a prior history of thromboembolism. In this setting, an alternative combinations of therapies including daratumumab, bortezomib, cyclophosphamide, and dexamethasone may be considered [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of recently published cases reported encouraging results with clonal directed treatment [ 12 14 ]; however, the experience from these cases showed that remissions were less likely to be durable if single drug regimens were used or if the treatment was discontinued prematurely, i.e. before the causative plasma cell clone was sufficiently eradicated.…”
Section: Discussionmentioning
confidence: 99%
“…While in patients with end-organ damage related to MM, immediate treatment is required and recommended according to international guidelines, the approach in avWS patients with MGUS or SMM without end-organ damage or formal treatment indications is less clear [ 11 ]. Several groups reported improvement or even normalization of MG-avWS following antimyeloma treatment [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%